Saucer county compendium ebook - Cornell, Paul (Image Comics, 2024)
SAUCER COUNTRY is a dark thriller that blends UFO lore and alien abduction with political intrigue, all set in the hauntingly beautiful Southwest. Experience the full story of alien abductee Arcadia Alvarado's campaign to be US President...and her search for the truth of what happened to her, in the comic that suggested there was Russian intervention in US politics way before it was cool! This complete collection compiles the entire SAUCER COUNTRY , SAUCER STATE , and the all-new concluding chapter, SAUCER COUNTRY: THE FINALE !